Membangun Kinerja Bisnis Melalui Keunggulan Bersaing pada UKM Manufaktur - Nitya Pinasthika Valeria (Jurnal Ilmiah Aset, 2017)
This study analyzed the effect of entrepreneurial orientation, environmental adaptability, creativity and innovation on competitive advantage to improve business performance. The formulation of the problem is how to create a competitive advantage to Improve business performance. Selected population in this study is the metal industry small and medium scale in District Ceper, Klaten regency totaling 295 industries. In general conclusions from the results of testing the model is applied to the metal industry small and medium scale in District Ceper, Klaten regency showed that competitive advantage can be achieved through entrepreneurial orientation, adaptability environment, creativity and innovation, where the competitive advantage resulting company can improve business performance. In addition to a competitive advantage, entrepreneurial orientation and creativity innovation can improve business performance. This study provides some of the limitations of the study and future research agenda that can be done in advanced research.